Exploring the Clinical Characteristics of Type 2 Diabetes Mellitus Patients with Pulmonary Tuberculosis Complications: A Retrospective Study at Awal Bros Hospital - Adiputera Qazzafi; Taseen Umar (Acta Psychologia, 2023)
This research explores the characteristics of Type 2 Diabetes Mellitus (T2DM) patients with complications of pulmonary tuberculosis (TB) through a retrospective observational study conducted at Awal Bros Hospital. The study examines demographic profiles, temporal dynamics of disease coexistence, treatment patterns, and associated complications among individuals grappling with both T2DM and pulmonary TB. Findings reveal a diverse demographic distribution and varying durations of T2DM and TB coexistence, emphasizing the need for personalized healthcare strategies. A correlation between poor glycemic control and the severity of TB complications underscores the importance of optimized diabetes management. Variations in treatment patterns highlight the potential benefits of integrated care approaches. The study's implications for clinical practice emphasize the adoption of comprehensive, patient-centered care and the optimization of treatment strategies. Moreover, the research provides valuable insights for guiding future investigations and informs targeted public health initiatives. These findings contribute to the global understanding of the dual burden of T2DM and pulmonary TB, offering a foundation for improved healthcare practices and interventions.